2014
DOI: 10.1002/chem.201304561
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Dual‐Doped Hierarchical Porous Carbon Foams as Efficient Metal‐Free Electrocatalysts for Oxygen Reduction Reactions

Abstract: Despite tremendous progress in developing doped carbocatalysts for the oxygen reduction reaction (ORR), the ORR activity of current metal-free carbocatalysts is still inferior to that of conventional Pt/C catalysts, especially in acidic media and neutral solution. Moreover, it also remains a challenge to develop an effective and scalable method for the synthesis of metal-free carbocatalysts. Herein, we have developed nitrogen and phosphorus dual-doped hierarchical porous carbon foams (HP-NPCs) as efficient met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
103
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 66 publications
2
103
0
Order By: Relevance
“…According to the survey spectra in Figure 4a, the U(VI)‐adsorbed product maintained all the peaks in the NPS‐GLCs except for two evident peaks at 382.4 and 393.1 eV, which correspond to newly generated U 4f 7/2 and U 4f 5/2 , thereby indicating that a significant number of U(VI) was adsorbed by the NPS‐GLCs 35. The P—O peaks at 133.6 eV and S—O at 168.2 eV in the UO 2 2+ ‐adsorbed NPS‐GLCs increased remarkably as compared to the bare NPS‐GLCs, suggesting that the P and S were oxidized along with UO 2 2+ adsorption 36. We maintained that the UO 2 2+ ions were fixed on the NPS‐GLCs through the strong covalent bonds of P—O—U and S—O—U.…”
Section: Resultsmentioning
confidence: 96%
“…According to the survey spectra in Figure 4a, the U(VI)‐adsorbed product maintained all the peaks in the NPS‐GLCs except for two evident peaks at 382.4 and 393.1 eV, which correspond to newly generated U 4f 7/2 and U 4f 5/2 , thereby indicating that a significant number of U(VI) was adsorbed by the NPS‐GLCs 35. The P—O peaks at 133.6 eV and S—O at 168.2 eV in the UO 2 2+ ‐adsorbed NPS‐GLCs increased remarkably as compared to the bare NPS‐GLCs, suggesting that the P and S were oxidized along with UO 2 2+ adsorption 36. We maintained that the UO 2 2+ ions were fixed on the NPS‐GLCs through the strong covalent bonds of P—O—U and S—O—U.…”
Section: Resultsmentioning
confidence: 96%
“…For performance optimization purpose, many reports revealed that the catalytic activity and stability of the catalysts could be improved by employing a porous carbon as the supporting matrix, which can maximize the electroactive surface area of catalysts and improve the rapid transport of other reactants (such as oxygen molecules) and reaction products (such as hydroxide ions) [14]. Carbon materials such as carbon black, carbon nanotubes (CNTs) and graphene have been used as the catalyst supports broadly due to their low costs, porous structures as well as good conductivities [15,16]. Moreover, conducting polymers such as polypyrrole (PPy), polyaniline (PANI) and polythiophene (PTh) have gained considerable attention over the past decades due to their unique chemo-physical properties and have been applied in electrocatalysis and electroanalysis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…(b) and (d), the N1s spectra of both samples are deconvoluted into five N species: graphitic-N (401.3 eV), pyrrolic/pyridone-N (400.7 eV), BeNeC (399.5 eV), pyridinic-N (398.4 eV) and BeN (397.7 eV)[16,36,37]. The content of defect sites is enhanced after NH 3 activation, which agrees well with the Raman results.…”
mentioning
confidence: 99%